METABOLIC CHANGES IN TOXIC LIVER DAMAGE AND THE POSSIBILITY OF THEIR CORRECTION: Ochilov A.K. - PhD Bukhara State Medical Institute, Bukhara. Uzbekistan, Ochilov A.K. (Лучшие интеллектуальные исследования, 2024)
therefore, the aim of this study was to study the effect of the combination of antioxidants of sodium selenite and vitamin E on the indicants of physical development during chronic intoxication with magnesium chlorate in the prepubertal period